Study of Commitment Items Quality Members Effect on Price Synchronism in Tehran Stock Exchange - Shekari, Morteza Doosti Seyyed; Jamshidinavid, Babak (International Journal of Economics and Financial Issues, 2017)
Accounting profit always as an exhibited item in financial statements has been considered by investors whom are attended as the most significant users of financial statements, so profit is a basis for the most economical decisions. In the research, effect of committing item quality members with price synchronism (a criterion to measure the proportional amount of corporating special information, which has been reflected in price) has been investigated in accepted corporations in Tehran stock exchange. In research, committing item quality members are independent variables and price synchronism is dependent variable. Price synchronism is an amplitude which shows industry and market returns and stock return differences in corporation level. The research is application based on its aim, is measuring and describing based on its performance and is one of the best. 127 corporations from 2010 to 2014 have been chosen by systematic deletion. To test research hypotheses panel data method and fixed effect method have been used. Research conclusions show that there is no relationship between involuntary commitment items qualities with price synchronism, but there is a meaningful direct effect between voluntary committing items with price synchronism for accepted corporations in Tehran stock exchange. Keywords: Commitment Items Quality, Involuntary Commitment Items Quality, Price Synchronism JEL Classifications: E37, E32, C53, C5